PENYULUHAN PENGUATAN RELASI ORANGTUA DAN ANAK MELALUI RE-EDUKASI NILAI KELUARGA KRISTEN DI GEREJA BETHEL INDONESIA BRIDE OF CHRIST BATAM - Gomgom Purba; Tahan Sitanggang; Junus Maradona Gultom; Sanggam Simanjuntak (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The problem of parent and child relations has hit Christian families which has an impact on the mentality of children who no longer respect their parents, also has an impact on not fearing God and of course affecting the spiritual cycle in the Christian family's journey today. Bethel Indonesia Bride Of Christ Batam Church sees that strengthening parent-child relationships in terms of Christian family values which contain ethics, morals and faith education, needs to be considered and improved by finding effective ways to achieve these goals. The purpose of carrying out this community service is to provide counseling on strengthening parent-child relationships through re-education of Christian family values. This activity was carried out in 2022 at Bethel Indonesia Bride Of Christ Batam Church. The method used is counseling to strengthen parent-child relations through re-education of Christian family values, monitoring through re-education of Christian family values. All stages have been carried out properly supported by high congregational participation.